THE HERMENEUTICAL STRATEGY AND PRIBUMISASI OF HADITH IN THE JAVANESE SYARAH OF MISBAH AL-ANAM FI TARJAMAH BULUGH AL-MARAM BY A. SUBKI MASYHADI - Su'aidi, Hasan; Dimyathi, Aniq (RIWAYAH, 2025)
This research analyzes the methodology of hadith commentary in the book Miṣbāḥ al-Anām fī Tarjamah Bulūgh al-Marām by A. Subki Masyhadi, a prolific scholar from Pekalongan. Utilizing a descriptive-qualitative method with content analysis techniques, this study reveals Masyhadi’s hermeneutical strategies in bridging authoritative classical texts with the socio-cultural realities of Javanese society. The findings indicate the use of a combined ijmālī (global) and muqārin (comparative) method, integrated through three primary approaches: textual, contextual, and intertextual. Masyhadi maintains the orthodoxy of the pesantren tradition by referencing the Qur'an, Shafi'i jurisprudential literature, and linguistic authorities such as al-Nihāyah and Subul al-Salām. The originality of Masyhadi’s work lies in its massive effort toward the "indigenization" (pribumisasi) of hadith. The use of the Arabic-Pegon script is not merely a technical choice but serves as an epistemological bridge for non-Arabic speaking communities. The localization of prophetic teachings is carried out creatively through the inclusion of regional nuances, such as utilizing the Rupiah currency in legal transactions, employing local foodstuffs (tape and beras jowo) as jurisprudential analogies, and validating rebana art as a cultural identity. This research contributes to the mapping of Islamic intellectual history in the Nusantara, demonstrating that vernacular hadith commentaries are vital instruments for maintaining religious continuity while serving as a form of creative adaptation in responding to Indonesia's local identity and realities. [Penelitian ini menganalisis metodologi syarah hadis dalam kitab Miṣbāḥ al-Anām fī Tarjamah Bulūgh al-Marām karya A. Subki Masyhadi, seorang ulama produktif asal Pekalongan. Menggunakan metode deskriptif-kualitatif dengan teknik analisis isi (content analysis), studi ini mengungkap strategi hermeneutika Masyhadi dalam menjembatani teks otoritatif klasik dengan realitas sosiokultural masyarakat Jawa. Temuan penelitian menunjukkan penggunaan kombinasi metode ijmālī (global) dan muqārin (komparatif) yang diintegrasikan melalui tiga pendekatan utama: tekstual, kontekstual, dan intertekstual. Masyhadi mempertahankan ortodoksi tradisi pesantren dengan merujuk pada Al-Qur'an, literatur yurisprudensi Syafi'i, serta otoritas linguistik seperti al-Nihāyah dan Subul al-Salām. Orisinalitas karya Masyhadi terletak pada upaya pribumisasi hadis yang masif. Penggunaan aksara Arab-Pegon bukan sekadar pilihan teknis, melainkan jembatan epistemologis bagi masyarakat non-Arab. Lokalisasi ajaran kenabian dilakukan secara kreatif melalui penyertaan nuansa regional, seperti penggunaan satuan mata uang Rupiah dalam transaksi hukum, pemanfaatan bahan pangan lokal (tape dan beras jowo) sebagai analogi fikih, hingga validasi seni rebana sebagai identitas kultural. Penelitian ini berkontribusi pada pemetaan sejarah intelektual Islam di Nusantara, menunjukkan bahwa syarah hadis vernakular merupakan instrumen vital dalam menjaga kontinuitas keagamaan sekaligus bentuk adaptasi kreatif Islam dalam merespons identitas dan realitas lokal Indonesia.]